Transverse colon perforation in the mediastinum after esophagectomy: a case report - Takuro Konno-Kumagai; Tadashi Sakurai; Yusuke Taniyama; Chiaki Sato; Kai Takaya; Ken Ito; Takashi Kamei (Surgical Case Reports)
Abstract Background While anastomotic leakage, recurrent laryngeal nerve paralysis, and pneumonia are well-known complications of esophagectomy, the incidence of hiatal hernia after esophagectomy for carcinoma has been reported to only be between 0.6 and 10%. We report a very rare case of hiatal hernia with transverse colon rupture in the mediastinum after esophagectomy in a 65-year-old woman. Case presentation The patient underwent definitive chemoradiotherapy for clinical stage IIA esophageal squamous cell carcinoma and salvage esophagectomy with gastric tube reconstruction through a posterior mediastinum route for residual carcinoma. Three years after the initial surgery, two metastatic nodules in the lateral and posterior segments of the liver were detected on follow-up CT and were treated with oral anticancer drugs. After 6 months, the patient was readmitted for anorexia. Upon admission, computed tomography revealed an ileus caused by a hiatal hernia. Emergent operative repair was performed; an incarcerated herniation of the transverse colon was perforated in the mediastinum, and partial transverse colon resection and colostomy were performed. Intensive care was required to control septic shock after surgery, and the patient was discharged on the 53rd postoperative day. Conclusions Cases of hiatal hernia with digestive tract prolapsing into the mediastinum after esophagectomy with reconstruction through posterior mediastinum are rare but potentially life-threatening complications.